ЕLECTROPHILIC SUBSTITUTION IN 6,8-DIARYL-1Н-IMIDAZO[1,2-a]PYRIDINIUM SALTS: UDC 547.821+ 547.781 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2017)
Imidazo[1,2-a]pyridine moieties have attracted much recent interest because of their broad range of pharmacological activities. Electrophilic substitution is increasingly used in recent years as a method of modifying their structure. This paper studied electrophilic substitution in the 1H-imidazo[1,2-a]pyridin-4-ium cation. Sulfonation and bromination reactions were investigated for imidazo[1,2-a]pyridinium derivatives with an aryl groups substituted at the pyridine cycle. We cjnfirmed that the main direction of electrophilic substitution in 1-alkyl-1H-imidazo[1,2-a]pyridin-4-ium cation, as in unsubstituted in position 1 derivatives, is position 3. The formation of substitution product on phenyl groups of the molecule is possible in the presence of unsubstituted in 4 position phenyl groups.The treatment of 6,8-bis(4-clorophenyl)-1-methyl-1H-imidazo[1,2-a]pyridin-4-ium bromide with HSO3Cl or H2SO4(c) gave 6,8-bis(4-clorophenyl)-1-methyl-3-sulfo-1H-imidazo[1,2-a]pyridin-4-ium halogenides. These results are similar to those for the reactions of 6,8-diaryl-1-methyl-1H-imidazo[1,2-a]pyridin-4-ium bromides with Br2 in AcOH, which gave 3-bromo-6,8-diaryl-1-methyl-1H-imidazo[1,2-a]pyridin-4-ium bromideses. However, the treatment of 6,8-diphenyl-1-methyl-1H-imidazo[1,2-a]pyridin-4-ium bromide with HSO3Cl provided a mixture of 1-methyl-6-phenyl-8-(4-sulfophenyl)-1H-imidazo[1,2-a]pyridin-4-ium and 1-methyl-6,8-diphenyl-3-sulfo-1H-imidazo[1,2-a]pyridin-4-ium halohenides (4 : 1) that could not be separated. The structure of products is proved by two-dimensional correlation spectroscopy NMR methods (COSY, NOESY, HMQC, HMBC).
Keywords: sulfonation; bromination; 1H-imidazo[1,2-a]pyridin-4-ium cation; 3-sulfoimidazo[1,2-a]pyridin; 3-bromoimidazo[1,2-a]pyridin